Analisis pemotongan logam ST-37 dengan mesin potong menggunakan gas oxy-LPG - Ade Irvan Tauvana; Widodo Widodo (Universitas Muhammadiyah Metro, 2020)
This gas cutting machine is an ST-37 metal cutting tool in a semi-automatic way using Liquified Potroleum Gas (LPG) and Oxygen gas materials. LPG gas is used with a composition of propane 80% and Isobutane 20%. In the process of cutting metal based on several parameters, namely: metal thickness, oxygen gas pressure, and LPG gas and cutting speed. Before cutting down the metal, the preparation stage is done by conditioning the test equipment and work equipment used to collect test data. The method used in this research is to select the type of metal and cutting equipment then do the recording and taking test data. Further analysis and examination are carried out as follows: visual inspection of the results of cutting and flame shape, a better composition results from testing in accordance with applicable rules such as pressure, plate thickness, and time of cutting. 80% and 20% LPG gas composition at gas working pressure: 0.2 kg / cm2, oxygen pressure: 2.5 kg / cm2, cutting distance of 2 mm. The results of this test are overall in good condition and no defects occur.Keywords: LPG Gas cutting, Propane, Isobutane, Cutting speed, oxygen.